Principles of Mobile Communication - Stüber, Gordon L.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This mathematically rigorous overview of physical layer wireless communications is now in a 4th, fully revised and updated edition. The new edition features new content on 4G cellular systems, 5G cellular outlook, bandpass signals and systems, and polarization, among many other topics, in addition to a new chapters on channel assignment techniques. Along with coverage of fundamentals and basic principles sufficient for novice students, the volume includes finer details that satisfy the requirements of graduate students aiming to conduct in-depth research. The book begins with a survey of the field, introducing issues relevant to wireless communications. The book moves on to cover relevant discrete subjects, from radio propagation, to error probability performance, and cellular radio resource management. An appendix provides a tutorial on probability and random processes. The content stresses core principles that are applicable to a broad range of wireless standards. New examples are provided throughout the book to better explain the more complex material to the reader. Additional problems have also been added to those already appearing at the ends of the chapters to make the book more suitable for course instruction. Provides an updated textbook for university graduate-level courses teaching mobile communications or wireless communication Offers a rigorous study in the fundamentals and principles of wireless communication, with homework problems throughout Includes new content on 4G cellular systems, 5G cellular outlook, bandpass signals and systems, and polarization among many other topics and a new chapter on channel assignment techniques.
Introduction -- Propagation Modeling -- Co-channel Interference -- Modulation and Power Spectrum -- Detection of Known Signals in Noise -- Multi-antenna Techniques -- Time Domain Equalization and Interference Cancelation -- Error Control Coding -- Spread Spectrum Techniques -- Multi-carrier Techniques -- Frequency Planning -- CDMA Cellular Networks -- Radio Resource Management -- Channel Assignment Techniques -- Probability and Random Processes -- Conclusion.
Keywords: Telecommunication; Signal processing; Computer input-output equipment; Communications Engineering, Networks; Signal, Speech and Image Processing .; Input/Output and Data Communications